A community-based initiative to improve transgender mental health in Canterbury, New Zealand - Rebecca Nicholls; Lisa McGonigle (CSIRO Publishing, 2022)
Background and context The transgender community experiences high levels of mental distress. In the Canterbury region of New Zealand, transgender care was fragmented and there were gaps in service provision. Assessment of problem In 2019, a working group co-designed a model to coordinate and improve health care for the Canterbury transgender community. Their aim was to co-design and implement a comprehensive system for transgender health care that filled any existing gaps. Results A need was identified for support in the community for transgender patients with mild to moderate mental health needs who did not meet the threshold for referral to secondary care. Strategies for improvement Psychological packages of care were put in place in the community for transgender patients with mental health needs. In the first 9 months of the initiative, 85 patients received a package of care. Lessons This community-based model was well received by the community. Data analysis did not demonstrate a statistically significant reduction in depression and anxiety, but it did show a significant reduction in stress. Some further improvement opportunities existed, including shifting to a peer worker model and changing the evaluation tool.